2019
DOI: 10.1111/jopy.12476
|View full text |Cite
|
Sign up to set email alerts
|

Who falls for fake news? The roles of bullshit receptivity, overclaiming, familiarity, and analytic thinking

Abstract: Objective Fake news represents a particularly egregious and direct avenue by which inaccurate beliefs have been propagated via social media. We investigate the psychological profile of individuals who fall prey to fake news. Method We recruited 1,606 participants from Amazon’s Mechanical Turk for three online surveys. Results The tendency to ascribe profundity to randomly generated sentences—pseudo‐profound bullshit receptivity—correlates positively with perceptions of fake news accuracy, and negatively with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
494
9
25

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 560 publications
(566 citation statements)
references
References 91 publications
(168 reference statements)
38
494
9
25
Order By: Relevance
“…Indeed, an abundance of evidence suggests that individuals assume they are being informed of the truth and are bad at identifying lies and misinformation (e.g., Bond & DePaulo, 2006;Levine, Park, & McCornack, 1999). This suggests that an over-reliance on intuition -and, specifically, having a reflexively open-minded thinking style (Pennycook & Rand, 2019c) -is likely to result in people being more susceptible to believing fake news. As we find, inducing emotional, intuitive reasoning does in fact increase the propensity to believe fake news stories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, an abundance of evidence suggests that individuals assume they are being informed of the truth and are bad at identifying lies and misinformation (e.g., Bond & DePaulo, 2006;Levine, Park, & McCornack, 1999). This suggests that an over-reliance on intuition -and, specifically, having a reflexively open-minded thinking style (Pennycook & Rand, 2019c) -is likely to result in people being more susceptible to believing fake news. As we find, inducing emotional, intuitive reasoning does in fact increase the propensity to believe fake news stories.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, analytic thinking is associated with lower trust in fake news sources (Pennycook & Rand, 2019b). Belief in fake news has also been associated with dogmatism, religious fundamentalism, and reflexive (rather than active/reflective) open-minded thinking (Bronstein et al, 2019;Pennycook & Rand, 2019c). A recent experiment has even shown that encouraging people to think deliberately, rather than intuitively, decreased self-reported likelihood of 'liking' or sharing fake news on social media (Effron & Raj, 2020), as did asking people to judge the accuracy of every headline prior to making a sharing decision (Fazio, 2020), or simply asking for a single accuracy judgment at the outset of the study Pennycook et al, 2020).…”
Section: Motivated Cognition Versus Classical Reasoningmentioning
confidence: 99%
“…Another preventative approach involves subtle prompts that nudge people to consider accuracy. Evidence suggests that deliberation is associated with [134][135][136] and causes 137 reduced belief in false news headlines that circulated on social media. Platforms could nudge users to think about accuracy by, for example, periodically asking users to rate the accuracy of randomly selected posts.…”
Section: Conspiracy Theoriesmentioning
confidence: 99%
“…On a more behavioral note, individuals high on bullshit receptivity were less likely to engage in prosocial behavior (e.g., to volunteer for a charity; Erlandsson, Nilsson, Tinghög, & Västfjäll, 2018). Finally, the paradigm of individual differences in pseudo-profound bullshit research was also extended by investigating the association with political attitudes: support for Republicans and conservatism (Pfattheicher & Schindler, 2016), neoliberalism (Sterling, Jost, & Pennycook, 2016), and proneness to fake news (Pennycook & Rand, 2018) or ideology in general (Nilsson, Erlandsson, & Västfjäll, 2019). However, given that previous research has yielded many similar findings, we suggest that changing the line of research might be more fruitful.…”
Section: Pseudo-profound Bullshitmentioning
confidence: 99%